2019
DOI: 10.1038/s41598-019-50783-z
|View full text |Cite
|
Sign up to set email alerts
|

Resource use efficiency of indoor lettuce (Lactuca sativa L.) cultivation as affected by red:blue ratio provided by LED lighting

Abstract: LED lighting in indoor farming systems allows to modulate the spectrum to fit plant needs. Red (R) and blue (B) lights are often used, being highly active for photosynthesis. The effect of R and B spectral components on lettuce plant physiology and biochemistry and resource use efficiency were studied. Five red:blue (RB) ratios (0.5-1-2-3-4) supplied by LED and a fluorescent control (RB = 1) were tested in six experiments in controlled conditions (PPFD = 215 μmol m−2 s−1, daylength 16 h). LED lighting increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 143 publications
(126 citation statements)
references
References 43 publications
9
113
3
1
Order By: Relevance
“…Thus, the green cultivars were the most stimulated by higher proportion of red light, while the red cultivars reacted the most with higher ratios of blue light. Pennisi et al 9 . showed that a combination of lights RB 0.5 (30% red, 58% blue) decreased the antioxidant activity and the total bioactive compounds (phenolics and chlorophyll), while a higher application of red light, RB 3 (>70% red, 23% blue), showed a promising increase of flavonoids and TPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the green cultivars were the most stimulated by higher proportion of red light, while the red cultivars reacted the most with higher ratios of blue light. Pennisi et al 9 . showed that a combination of lights RB 0.5 (30% red, 58% blue) decreased the antioxidant activity and the total bioactive compounds (phenolics and chlorophyll), while a higher application of red light, RB 3 (>70% red, 23% blue), showed a promising increase of flavonoids and TPC.…”
Section: Discussionmentioning
confidence: 99%
“…The technological advancements in LED technology have resulted in its widespread application in horticultural production systems, due to its limited thermal dissipation, its low energy requirements and the possibility of finely customizing light intensity and spectral properties 8 . For instance, during plant cultivation, modulating red and blue spectral components was recently shown to influence the antioxidant profile of basil, 8 lettuce, 9 rocket, 10 dill and parsley 11 . Moreover, quantity and quality of light were also shown to alter pathogenic plant interactions in strawberry, by acting on both plant tissues and pathogens 7 .…”
Section: Introductionmentioning
confidence: 99%
“…LED application of red and blue fractions using LED lamps improved the accumulation of antioxidant phenolic compounds for lettuce plants compared with those under fluorescent lamp [17]. LED lighting treatment enhanced energy use efficiency (176%) and energy yield (9%) of lettuce plants when compared with fluorescent lamps [18,19]. No significant differences between white LEDs and cool white fluorescent lamps were found for all physiological and yield parameters of lettuce plants.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, the spectral changes of the red and blue lights influenced the uptake of Fe and Zn [54]. Another study investigated the effects of the red and blue spectral components in lettuce [55]. In this case, a predominant fraction of the red raised the concentration of N, P, K, and Mg in lettuce leaves.…”
Section: Discussionmentioning
confidence: 99%